2016
DOI: 10.1038/srep29782
|View full text |Cite
|
Sign up to set email alerts
|

Detection of methoxylated and hydroxylated polychlorinated biphenyls in sewage sludge in China with evidence for their microbial transformation

Abstract: The concentrations of methoxylated polychlorinated biphenyls (MeO-PCBs) and hydroxylated polychlorinated biphenyls (OH-PCBs) were measured in the sewage sludge samples collected from twelve wastewater treatment plants in China. Two MeO-PCB congeners, including 3′-MeO-CB-65 and 4′-MeO-CB-101, were detected in three sludge with mean concentrations of 0.58 and 0.52 ng/g dry weight, respectively. OH-PCBs were detected in eight sludge samples, with an average total concentration of 4.2 ng/g dry weight. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Polychlorinated biphenyls (PCBs) belong to persistent organic pollutants (POP) 1 for their toxicity and stability against degradation in soil and water 2 , 3 . In the past decades, various technologies have been developed carried out about degradation of PCBs and its bioaccumulation 4 , 5 . Within all the methods used to degrade the PCBs, laccase was considered as an efficient route to solve the problem because the phenolic compounds were the major substrates of laccase 6 , 7 , and amount of results showed that the laccase can efficiently remove the PCBs pollutants from the water 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Polychlorinated biphenyls (PCBs) belong to persistent organic pollutants (POP) 1 for their toxicity and stability against degradation in soil and water 2 , 3 . In the past decades, various technologies have been developed carried out about degradation of PCBs and its bioaccumulation 4 , 5 . Within all the methods used to degrade the PCBs, laccase was considered as an efficient route to solve the problem because the phenolic compounds were the major substrates of laccase 6 , 7 , and amount of results showed that the laccase can efficiently remove the PCBs pollutants from the water 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Sun et al (2016) detected OH-PCBs in sewage sludge in China. 12 We also reported OH-PCBs in sediments from the Indiana Harbor and Ship Canal in Indiana, USA (IHSC), in . 10 To our knowledge, there are no studies of the full suite of OH-PCBs in sediments but only small sets of those with standards available.…”
Section: ■ Introductionmentioning
confidence: 90%
“…For instance, Rice ( Oryza sativa L. ) was reported to metabolize PCB61 into para -substituted hydroxylated PCB61 as its major metabolite, along with a minor product of para -substituted methoxy PCB61 . In addition, the microbial transformation of PCBs into hydxylated and methoxy PCBs was also proposed. , Pham et al reported a hydroxylation of PCBs with an initial attack by the biphenyl dioxygenase from wild-type strains P. pnomenusa B356 . The hydroxylated metabolites produced from para -substituted biphenyl analogs 4′-PCB-4-ol, through a 2,3-dioxygenation of the hydroxylated ring, ultimately lead to 4′-PCB-3,4,5-ol.…”
Section: Metabolic Pathway Yielding Hydroxylated and Quinone-type Met...mentioning
confidence: 99%
“…77 In addition, the microbial transformation of PCBs into hydxylated and methoxy PCBs was also proposed. 78,79 Pham et al reported a hydroxylation of PCBs with an initial attack by the biphenyl dioxygenase from wild-type strains P. pnomenusa B356. 80 The hydroxylated metabolites produced from parasubstituted biphenyl analogs 4′-PCB-4-ol, through a 2,3dioxygenation of the hydroxylated ring, ultimately lead to 4′-PCB-3,4,5-ol.…”
Section: Metabolic Pathway Yieldingmentioning
confidence: 99%